2022
DOI: 10.3390/jmse10020262
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Salt Intrusion and Estuarine Plumes under Climate Change Scenarios in Two Transitional Ecosystems from the NW Atlantic Coast

Abstract: The Minho and Lima estuaries, separated by approximately 20 km, are two important transitional systems from the NW Atlantic Portuguese coast. Considering their contrasting characteristics, the present work aims to investigate climate change impacts in salt intrusion and estuarine plumes interaction, through an integrated hydrological characterization. The three-dimensional numerical model Delft3D was implemented to explore the hydrological response of these two systems taking into account their interaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…These results are in line with the results found by Liu and Liu, 2014;Duvall et al, 2022;Pereira et al, 2022 andCosta et al, 2023, where the increase of salinity intrusion in the estuaries is reported due to sea level rise. It is important to point out that the salinity and density in the Suances estuary are strongly related and the changes in temperature will be minimal as shown in Table 3.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in line with the results found by Liu and Liu, 2014;Duvall et al, 2022;Pereira et al, 2022 andCosta et al, 2023, where the increase of salinity intrusion in the estuaries is reported due to sea level rise. It is important to point out that the salinity and density in the Suances estuary are strongly related and the changes in temperature will be minimal as shown in Table 3.…”
Section: Discussionsupporting
confidence: 93%
“…This phenomenon will decrease the freshwater input to the estuary and increase the tidal excursion along the estuary, producing a displacement of the river/estuarine front upstream in line with the results observed by Ma et al, 2023. As shown in Figure 8, the starting point of the stratification zone moves upstream of the estuary in the projected scenarios as seen in the Minho estuary in Pereira et al, 2022 and the Wu river in Liu and Liu, 2014, where salinity intrusion extends more than 2.000 m and 900 m in the projected scenarios, respectively. In the Minho and Wu estuaries, sea level rise is the main cause of increased salinity intrusion.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The sea level rise will increase the depths, reducing the tidal marshal zones, making mixing and stratification processes in these areas more likely to occur. The reason behind these causes is the fact that sea level rise will increase the water column, and therefore create more pronounced stratification patterns back inland from the estuary as seen in the various studies analyzed in the region surrounding the study area, such as the NW Atlantic coast of Portugal [66,67] or the UK coast [68]. This is especially noticeable in the intertidal zones, where in the 2020 scenario there were fully mixed zones that have now been replaced by weakly stratified zones.…”
Section: Dynamic Classification Of Estuarine Vertical Structure and P...mentioning
confidence: 93%